Tributação com finalidade extrafiscal: entre a confiscatoriedade e o desenvolvimento econômico-social - Santos, Jerônimo Dix-neuf Rosado dos (2015)
This study aims to analyze the use of tax extrafiscality as a means available to the Brazilian Government able to improve economic and social development, with greater emphasis on correct and maximum use of real estate achieving its social function (IPTU e ITR), in contrast to the benchmarks constitutional principles of the entire system. In analyses of the proposed theme, we will study the constitutional system, with an emphasis on constitutional principles, moving even to the infra-constitutional legislation applied to the theme, including the modern doctrine and jurisprudence of our Federal Supreme Court. We'll explore tax norms, its characteristics and its relationship both with the principle of non-conficatory, as with extrafiscality. We are will proceed investigating some other forms of extrafiscal use of taxes as a tool for economic and social development. We will focus on the end in the primer object of this research work, which lies in the possibility of using exactions to fiscal or extrafiscal character, in his eagerness to promote the better use / land use - rural or urban, without, however, be extrapolated permission and constitutional limits, invading greatly guidelines of the entire system and guarantors of the most precious individual and collective rights. It is the deepening study about the social function of real state properties in line with the constitutional system as a means able to sketch a problem outline for an economic and social future that has already arrived in the country. We seek so without flanking the maximum printed in the canons of Laws Act, the confrontation between extrafiscality and the principle of non-confiscatory, while we will check the need for a balanced co-existence and economic and social development tool